Macrophage-fibroblast JAK/STAT dependent crosstalk promotes liver metastatic outgrowth in pancreatic cancer - Raymant, Meirion; Astuti, Yuliana; Alvaro-Espinosa, Laura; Green, Daniel; Quaranta, Valeria; Bellomo, Gaia; Glenn, Mark; Chandran-Gorner, Vatshala; Palmer, Daniel H.; Halloran, Christopher; Ghaneh, Paula; Henderson, Neil C.; et al. (Nature communications, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is a highly metastatic disease for which better therapies are urgently needed. Fibroblasts and macrophages are heterogeneous cell populations able to enhance metastasis, but the role of a macrophage-fibroblast crosstalk in regulating their pro-metastatic functions remains poorly understood. Here we deconvolve how macrophages regulate metastasis-associated fibroblast (MAF) heterogeneity in the liver. We identify three functionally distinct MAF populations, among which the generation of pro-metastatic and immunoregulatory myofibroblastic-MAFs (myMAFs) critically depends on macrophages. Mechanistically, myMAFs are induced through a STAT3-dependent mechanism driven by macrophage-derived progranulin and cancer cell-secreted leukaemia inhibitory factor (LIF). In a reciprocal manner, myMAF secreted osteopontin promotes an immunosuppressive macrophage phenotype resulting in the inhibition of cytotoxic T cell functions. Pharmacological blockade of STAT3 or myMAF-specific genetic depletion of STAT3 restores an anti-tumour immune response and reduces metastases. Our findings provide molecular insights into the complex macrophage–fibroblast interactions in tumours and reveal potential targets to inhibit PDAC liver metastasis. An inflammatory-fibrotic tumor microenvironment supports metastatic disease progression in pancreatic ductal adenocarcinoma (PDAC). Here the authors show that metastasis-infiltrating macrophages influence metastasis-associated fibroblast (MAF) heterogeneity in liver metastatic PDAC, by promoting JAK/STAT signalling pathway activation in MAFs.